### Solving quadratics of the form ax^{2} + bx + c = 0 − using the quadratic formula

Solving quadratics of the form ax^{2} + bx + c = 0 using the quadratic formula:

x = |

#### Example 1. Solve 2x

^{2}+ 12x + 10 = 0#### Example 2. Solve 4x

^{2}− 11x + 6 = 0#### Example 3. Solve 2x

^{2}+ 2x − 24 = 0#### Example 4. Solve 3x

^{2}− 4x − 20 = 0

x = |

Verify by putting these two values of x into 2x^{2} + 12x + 10

x = |

Check by putting these two values of x into 4x^{2} − 11x + 6

x = |

Verify by putting these two values of x into 2x^{2} + 2x − 24

x = |

Check by putting these two values of x into 3x^{2} − 4x − 20

#### Remember:

Find the values of x where ax^{2} + bx + c = 0 is the same as solve ax^{2} + bx + c = 0

to: